(untitled) (Research, Society and Development, 2021)
The prescription drug is a fundamental tool that can avoid the irrational use of medicines minimizing the risks and favoring its benefits, therefore, it must be understood by the user so that its objectives are reached. - to assess the level of knowledge of Primary Health Care (PHC) users about their prescriptions, as well as to outline the population’s socio-demographic profile, to characterize and discuss the main factors that influence this problem. The study is a field research with a quantitative approach carried out in the context of PHC. Data were collected through an interview with 210 participants who had a prescription issued by a nurse, doctor or dentist. The research started after approval by the Ethics Committee, ensuring the participants’ rights in accordance with ethical and legal aspects. The results showed that the population studied is mostly female, elderly and low income. Regarding understanding, it was possible to observe a great deficiency in the knowledge about possible drug interactions and adverse reactions, followed by the time of treatment and name of the drug, revealing the rich that users are exposed due to the ineffective understanding of their prescriptions. Thus, it is concluded that there is a need to prepare the prescribing professionals to carry out a rational prescription, instructing users more effectively on the follow-up of their drug therapy, which makes it possible to minimize their risks and promote the Rational Use of Medicines.